MEKANISME ANTAGONISME BEBERAPA ISOLAT JAMUR ANTAGONIS TERHADAP PERTUMBUHAN JAMUR Colletotrichum gloeosporioides - rosyida, risya (BUANA SAINS, 2025)
The pathogen Colletotrichum gloeosporioides causes anthracnose disease in cayenne pepper, which is difficult to control. It is expected to control the pathogen by using antagonistic fungi because it has the ability to stop its growth by means of antibiosis, parasitism, or competition. This study aims to test five isolates of antagonistic fungi for their ability to inhibit C. gloeosporioides, which causes anthracnose disease in cayenne pepper plants, and to identify the mechanism of inhibition in vitro. Inhibition and antagonistic mechanisms were used in the study. Each test used a full-randomized design. The antagonistic fungi used were Aspergillus sp., Penicillium sp., Gliocladium sp., Nigrospora sp., and Trichoderma sp., each repeated five times. The results showed that, compared to the other fungi, the antagonistic fungal isolate Trichoderma sp. had a high inhibitory ability (74%). The three isolates of antagonistic fungi have antagonistic mechanisms against C. gloeosporioides, namely Aspergillus sp., Gliocladium sp., and Trichoderma sp. In addition, isolates of Gliocladium sp., Nigrospora sp., and Trichoderma sp. also have parasitism ability, while Aspergillus sp., Penicillium sp., and Trichoderma sp. have antibiosis mechanisms against C. gloeosporioides. Antagonistic fungal isolates that have the most potential to be developed as biological agents for anthracnose control in cayenne pepper plants, namely Trichoderma sp.